The impact of low-cost airlines on Madeira Islands - Gonçalves, Sérgio (2010)
This study identifies the short term impacts of Low-Cost Airlines (LCAs) on Madeira Islands. By analysing the relevant literature, this study describes the interdependence between tourism and air transport, and the effect that the low-cost airline concept has on both industries. Both generic and industry specific impacts are drawn from the literature, while explaining the advantages and disadvantages of this airline business model. LCAs have experienced tremendous growth in Europe since its birth in the mid 1990’s and have now reached Madeira Islands, a tourism destination still served mainly by charter operations offering tour operator’s package holidays. Research made out of airport and tourism statistics, shows evidence of a significant mismatch between offer and demand in the tourism industry that could possibly be diminished by the entry of LCAs in the market. Findings suggest that, as previously observed for other regions, LCAs do in fact generate significant airport passenger growth, therefore increasing the number of tourists visiting the islands and spending nights at the hotels. However, the average length of stay decreases as more flight frequency induces flexibility and shot-break vacations. While long term impacts are yet to be measured, in order to achieve a balance between tourism supply and demand, as well as higher economic development, all players in the market must join efforts in developing strategies that will promote sustained growth.